INTERNATIONAL TRADE IN SERVICES OF LVIV REGION: ANALYTICAL ASPECT - Brukh О.; Lyndiuk А.; Boiko В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Modern global trends indicate the growing role and significance of the services sector in ensuring social development in the context of the world economy globalization. Today, the study of the essence of services, analysis, and dynamics of structural changes in the market is very important and relevant. It is worth noting that this sector performs on the economic principles that necessitates comprehensive analysis of both financial and economic indicators. Therefore, the study of trends and peculiarities of the service market development, its constant diversification, encompasses various aspects and components. The purpose of this article is to present the results of the analysis of Ukraine's international trade in terms of export-import activities. The paper provides the world ranking of countries by the indicator of trade turnover with Ukraine in 2022, determines the share of each country in the total trade turnover with Ukraine, and identifies the difference between imports and exports for the corresponding period of time. The research is focused on the dynamics of international activities of Lviv region during 2019–2022 and the impact of military aggression in 2022 on this dynamics. The structure of Lviv region's foreign trade in services for 2022 is analyzed in terms of individual service sectors, and the dynamics of changes in the foreign trade in specific types of services are demonstrated as compared to 2021 and 2022. The authors of the article analyze and specify the main geographical partners in the structure of service exports and imports. The world ranking of countries by the indicator of service exports and imports of Lviv region in 2022 is developed, identifying the region's main partners in the field of trade in services and evaluating the dynamics of their cooperation. It is revealed that service exports and imports of the Lviv region have shown a tendency of stable growth during the investigated period, while the commodity and geographical structures undergone changes. The largest volumes of exports and imports are marked in the fields of transport, telecommunications, computer, and information services.